Peran Manitol dalam Penanganan Peningkatan Tekanan Intrakranial pada Stroke Non-Hemoragik dengan Penyakit Jantung Bawaan: Laporan Kasus - Putu Indah Mahardika Putri; I Wayan Widyantara (PT Dexa Medica, 2026)
Background: Stroke is a condition of impaired cerebral circulation leading to brain tissue necrosis. It is the second leading cause of death worldwide after heart disease. Nonhemorrhagic stroke may result from thrombus formation or embolic occlusion. Congenital heart disease (CHD) is one of the risk factor for stroke, including tetralogy of Fallot (TOF). The incidence of stroke in CHD is approximately 1 in 11 males and 1 in 15 females. One of the complications of stroke is increased intracranial pressure (ICP). Mannitol is one of treatment that can be used to reduce elevated intracranial pressure (EICP). Case report: A 19-year-old male with a history of TOF presented with decreased consciousness and left-sided hemiparesis. A CT scan revealed a hypodense lesion suggestive of ischemic stroke. On the third day of hospitalization, the patient’s condition worsened, showing signs of increased ICP. A repeat CT scan showed hemorrhagic transformation accompanied by uncal herniation. Mannitol was administered for 3 days to manage the increased ICP, resulting in clinical improvement. Three days later, the patient was discharged with improved condition. Conclusion: The use of mannitol in stroke cases with CHD, such as TOF, showed favorable outcomes without causingadverse effects or worsening the underlying cardiac condition. Mannitol may be considered in patients with cardiac comorbidities.